PERLINDUNGAN HUKUM BAGI PENYEWA DALAM PERJANJIAN SEWA MENYEWA LAHAN AKIBAT ADANYA WANPRESTASI YANG DILAKUKAN OLEH PEMILIK LAHAN - Ni Made Liana Dewi (Kerta Dyatmika, 2019)
ABSTRACTLand leases have become commonplace in society and are implemented through written agreements with the aim of providing legal certainty, but disputes in land leases occasionally take place as civil disputes over land may result from the transfer of land rights, for example by sale and purchase agreements, leases, inheritance and so on. Disputes that occur in land lease agreements can occur various factors due to the parties in the agreement that did default. The formulation of the issues raised in this study is how fairness for tenants due to wanprestasi done by landowners and how the efforts can be made by the tenant due to the existence of default by landowners. This type of research is empirical legal research moving from the dispute that occurred in land lease agreements can occur various factors due to the parties in the agreement that did wanprestasi. This study examines the problem being reviewed from legal perspective by conducting research which emphasize on empirical nature that is direct field study that is at Bali International Medical Center Kuta Hospital. The conclusion of this research is the legal protection for the tenants because the wanprestasi done by the land owner is between the landowner and the tenant of the land made in the agreement and proclaims that they have entered into an agreement and asked the Notary to make a deed, then this deed is a deed made in the presence of a Notary (Notarial Deed), the Contracting Party having legal certainty and, therefore, a dispute in the execution of the treaty, the judge with his / her decision may apply so that the infringing party shall file the right and suit according to the agreement. Legal efforts that can be made by the lessee due to a default by landowners who feel aggrieved due to a default can apply for the fulfillment of the agreement, cancellation of the agreement or to seek redress for the defauding party. Determination of wanprestasi is built on a letter from the debtor to the creditor who is usually in the form of a warning (reprimand) The minimum duration has been made three times by the tenant of the land. If the notation is ignored, the land tenant is entitled to take the matter to court. And it is the courts who will decide whether or not the separation of defaults. Somation is a reprimand from the debtor to the debtor in order to fulfill the achievement in accordance with the contents of the agreement that has been agreed between the twoKeywords: Legal protection, tenant, land lease agreement, wanpraration by landowner.